Experimental investigation of oscillating heat pipe efficiency for a novel condenser by using Fe3O4 nanofluid - Davari, Hadi; Goshayeshi, Hamid Reza; Öztop, Hakan Fehmi; Chaer, Issa (Springer, 2020)
This paper presents a novel study on the performance of closed-loop oscillating heat pipe (CLOHP) using iron oxide (Fe3O4) as the working fluid for three types of condensers. The tested CLOHP consists of six turns made of copper tubes, 4.5 mm outer diameter and 3 mm inner diameter with heating power input in a range of 0-200 W. The experimental results showed that the thermal performance of the CLOHPs has been improved when the corrugated horizontal condenser was used compare to straight and corrugated vertical condensers. Based on 800 sets of available experimental data, the results show that the CLOHPs with corrugated horizontal condenser had better thermal performance when charged with Fe3O4/water at 2% mass concentration.
Keywords: Oscillating heat pipe; Heat resistant; Thermal efficiency; Nanofluid; Corrugated horizontal condenser